AI, Consciousness, and the Evolutionary Frontier: A Buddhist Reflection on Science and Human Futures - Peter D. Hershock (Religions)
The technological advances and material control that have resulted from reductive and deterministic practices of science are quite real. The digitally mediated expansion of experiential freedoms-of-choice and the transformative problem-solving potential of artificial intelligence are undeniable. But for all its successes, reductive physicalism has failed to solve the so-called hard problem of consciousness. As a result, its successes are exposing humanity to an intensifying confluence of existential and ethical risks as the digitally mediated attention economy and intelligent technology facilitate a fundamental restructuring of the dynamics of human presence. Making use of Buddhist conceptual resources and drawing out their implications regarding causality and agency, this paper offers a nondualist and nonreductionist approach to theorizing consciousness and evolutionary dynamics in ways that are suited to opening an ethically productive “middle path” to critically rethinking the so-called Fourth Industrial Revolution and more positively configuring the evolution human–technology–world relations.